C–H insertion as a key step to spiro-oxetanes, scaffolds for drug discovery - Nicolle, Simon M.; Nortcliffe, Andrew; Bartrum, Hannah E.; Lewis, William; Hayes, Christopher J.; Moody, Christopher J. (Wiley, 2017)
A new route to spiro-oxetanes, potential scaffolds for drug discovery, is described. The route is based on the selective 1,4-C–H insertion reactions of metallocarbenes, generated from simple carbonyl precursors in flow or batch mode, to give spiro-β-lactones that are rapidly converted into spiro-oxetanes. The three-dimensional and lead like-properties of spiro-oxetanes is illustrated by the conversion of the 1-oxa-7-azaspiro[3,5]nonane scaffold into a range of functionalized derivatives.